Moderating Role of Audit Quality in GCG, Financial Distress, and Tax Avoidance - Surjadi, Julisar; Rudyanto, Astrid; Edgina, Mendy (Jurnal ASET (Akuntansi Riset), 2026)
Purpose: The purpose of this study is to determine whether audit quality can serve as a moderator between good corporate governance (GCG), financial distress, and tax avoidance. Profitability and firm size are used as control variables in this study. Design/methodology/approach: Using 68 manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2019-2021, this study employed quantitative analysis with Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis using WarpPLS 7. Findings: Audit quality in this study can serve as a moderating variable. The Control variable, the Return on Asset indicator, has a direct influence on Financial Distress and Tax Avoidance. However, control (Profitability) has a negative impact on Tax Avoidance. Originality/value: The finding that Audit Quality is able to moderate the relationship between Audit Committee and Tax Avoidance indicates that high-quality external auditors can increase the effectiveness of supervision and accountability.